2016
DOI: 10.1182/blood.v128.22.2358.2358
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Transplant: A Cost Effective and Efficacious Treatment for Newly Diagnosed Multiple Myeloma

Abstract: Background: Induction chemotherapy followed by autologous stem cell transplantation (ASCT) is considered a standard of care for appropriate patients with newly diagnosed multiple myeloma (MM), but with the rapid expansion of available treatments, the role of ASCT has been questioned. Numerous studies have shown an improvement in complete response (CR) and progression free survival (PFS) with ASCT but our study is a cost comparison between novel agents and ASCT. We aimed to compare the cost effectiveness of ASC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The 1-years PFS of 50% and 3-year OS of 68% achieved with ACHT2 in our study indicates clinical benefit. Additionally, AHCT2 is likely a cost-effective option compared to other expensive novel combinations available in relapsed setting 10 . However, most centers collect enough stem cells for >1 transplant, and a recent study from a single center reported a high cost of storage of those cells, but with low utilization rate suggesting potential underutilization of AHCT2 11 .…”
Section: To the Editormentioning
confidence: 99%
“…The 1-years PFS of 50% and 3-year OS of 68% achieved with ACHT2 in our study indicates clinical benefit. Additionally, AHCT2 is likely a cost-effective option compared to other expensive novel combinations available in relapsed setting 10 . However, most centers collect enough stem cells for >1 transplant, and a recent study from a single center reported a high cost of storage of those cells, but with low utilization rate suggesting potential underutilization of AHCT2 11 .…”
Section: To the Editormentioning
confidence: 99%
“…With the patent running out on lenalidomide and other viable, less costly maintenance approaches, such as bortezomib, under investigation, the proportional cost of an approach incorporating ASCT may very well decrease in the near future. In the study by Niphadkar et al [76], the estimated cost of ASCT was $109,856 § $5749.83, whereas just 1 month of novel doublet or triplet therapy ranged from as low as $9903 (bortezomib and dexamethasone) to as high as $27,422 (carfilzomib, lenalidomide, and dexamethasone). To further reduce costs and improve patients' quality of life, some centers are increasingly shifting ASCT to the outpatient setting.…”
Section: Additional Considerations: Cost Of Care and Quality Of Lifementioning
confidence: 99%
“…Thus, the ideal cost-effective treatment for relapsed MM following upfront ASCT should focus on PFS and thus may be SAT. Furthermore, Niphadkar et al [76] evaluated the cost-effectiveness of ASCT for MM and showed that in a novel treatment approach incorporating lenalidomide followed by ASCT and lenalidomide maintenance, the cost of induction and transplantation accounts for only 22% of the overall costs, with a substantial portion of this cost associated with the lenalidomide maintenance portion. With the patent running out on lenalidomide and other viable, less costly maintenance approaches, such as bortezomib, under investigation, the proportional cost of an approach incorporating ASCT may very well decrease in the near future.…”
Section: Additional Considerations: Cost Of Care and Quality Of Lifementioning
confidence: 99%